Cultural Processes Shaping Stop-and-Check Practices and Interaction Dynamics in a Large Dutch City: Police Vulnerabilities, Thought Styles and Rituals - Brown, Patrick (The British journal of criminology, 2021)
Existing scholarship on police decision-making notes the importance of categories and ‘governing mentalities’ in shaping front-line discretionary practices. Much of this work explores categories of race and ethnicity. Important questions remain regarding how micro-level practices connect to organizational dynamics and why ethnic profiling endures despite attempts to counter such practices. Drawing on critical approaches to uncertainty and risk, not least Mary Douglas’s cultural theory, we analyse data drawn from an ethnographic study of police work in a large city in the Netherlands. Our analysis emphasizes the multiple lines of accountability that render officers vulnerable in different ways, officers’ combining of different rationalities of decision-making and the influence of everyday rituals that cultivate and reinforce particular organizational thought styles and discretionary practices.